Syntactical Error Made by EFL Learners’ in Writing Descriptive Text - Ismi Umami, Lathifah Triya; Afrida, Lia Nur; Maghfiroh, Nazilatul; Hidayah, Nur Aisyatul; Afifah, Rif'atul; Agustina, Zeinita; Laili, Putri Nur; Adi Pranata, Muhammad Sofyan (International Journal of English Education and Linguistics (IJoEEL), 2023)
This study aims to identify the syntactical errors in the descriptive text writing of 10 elementary-level students at Al-Ikhlas Boarding School. This study applied a qualitative-descriptive approach. The source of data was taken from the students writing. Those descriptive texts were analyzed by classifying the errors as types of syntactical errors. From this study, the researcher found syntactical errors, namely errors in pronouns, be, plurals, and the use of the verb tense. This finding shows that EFL learners cannot completely master and apply the grammar of English in terms of syntactical function to their writing. It is influenced by factors such as interlingual and intralingual transfer. But the dominant factor in these results is interlanguage transfer. This study is supposed to be a reference for another researcher, linguist, and educator for their further study on error analysis.